Analisis Life Skills Mahasiswa Kimia pada Mata Kuliah Kimia Pangan Berbasis Chemo-Entrepreneurship - Imranah, Imranah; Muharram, Muharram; Anwar, Muhammad (Chemistry Education Review (CER), 2020)
This research used descriptive method with quantitative approach. This study aims to determine the life skills of chemistry students in the Food Chemistry based on chemo- entrepreneurship approach. The subjects in this study were chemistry students in the 5th semester of Mathematics and Natural Science Faculty State University of Makassar, that are 114 students. Data collection techniques used were questionnaires, observation, interviews, and documentation. The results showed that aspects of life skills obtained were generic life skills consisting of personal skills and social skills and specific life skills consisting of academic skills and vocational skills. As for each skill the results obtained are personal skills with 78.43 in the good category, social skills with 84.48 in the excellent category, academic skills with 75.00 in the good category, and vocational skills with 74.14 in the good category.